Retinal pigment epithelium cell density in relationship to axial length in human eyes - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2017)
To assess associations between axial length and density of retinal pigment epithelium (RPE) cells in various ocular regions.The histomorphometric investigation included histological sections of enucleated eyes of Caucasian patients. Using a light microscope, we counted the number of RPE cells on Bruch's membrane at the ora serrata, in the pre-equatorial region, the equatorial and retro-equatorial region, at the midpoint equator/posterior pole, and at the posterior pole.The study included 65 globes with a mean axial length 25.9 ± 3.5 mm (range: 21.0-34.0 mm). Retinal pigment epithelium (RPE) cell count in the equatorial to retro-equatorial region (p < 0.001; correlation coefficient r(2) : 0.44), in the pre-equatorial region (p < 0.001; r(2) : 0.39) and at the midpoint equator/posterior pole (p = 0.03; r(2) : 0.12) decreased with increasing axial length. Retinal pigment epithelium (RPE) cell count at the ora serrata (p = 0.49) and posterior pole (p = 0.44) was not significantly correlated with axial length. As a corollary, mean RPE cell density was higher (p < 0.001) at the posterior pole than at the midpoint equator/posterior pole or at the ora serrata region, where it was higher than in pre-equatorial region (p < 0.001) and in the equatorial to retro-equatorial region (p < 0.001).The decrease in the RPE cell density mainly in the equatorial to retro-equatorial region in association with longer axial length suggests a region of enlargement of Bruch's membrane in the equatorial to retro-equatorial area in association with axial elongation. The finding may be of interest to elucidate the process of emmetropization/myopization.
EVALuna2:21313